Management of Disaster News Content through the Regional Disaster Management Agency Website of Sleman Regency - Puji Lestari; Sri Isworo Ediningsih; Lita Yulita Fitriyani; Priyahita Garmadyuti Suryawijaya; Vanissa Zera Ardiyanti (Ikatan Sarjana Komunikasi Indonesia, 2024)
The Regional Disaster Management Agency (BPBD) in Sleman Regency now uses its website for quick and accurate disaster communication. However, the website content needs improvement to play its crucial role effectively. This study assesses the management of disaster news content on the BPBD Sleman Regency website by employing a mix of quantitative and qualitative methods. Data was collected through a variety of methods including FGD, simulations, interviews, and website observations. Analysis encompasses data reduction, presentation, and conclusion. Quantitative data includes percentage scoring from questionnaires distributed to website managers, contributors, BPBD secretariat, and the public. Qualitative data comprises descriptions from FGD, observations, and interviews conducted on August 2, 2022.Â The result showed that BPBD Sleman Regency has two websites, managed separately by the secretariat and TRC teams. The evaluation revealed that 51.8% of the community need the website for disaster information, and 87.1% find it easy to access the website. However, improvements are needed to optimize the website for quality information delivery and disaster communication. This study offers recommendations including Â enhancing HR competence for website management and community socialization to enhance disaster information services.